Historical H1N1 Influenza Virus Imprinting Increases Vaccine Protection by Influencing the Activity and Sustained Production of Antibodies Elicited at Vaccination in Ferrets - Magen E. Francis; Mara McNeil; Nicholas J. Dawe; Mary K. Foley; Morgan L. King; Ted M. Ross; Alyson A. Kelvin (Vaccines, 2019)
Influenza virus imprinting is now understood to significantly influence the immune responses and clinical outcome of influenza virus infections that occur later in life. Due to the yearly cycling of influenza viruses, humans are imprinted with the circulating virus of their birth year and subsequently build a complex influenza virus immune history. Despite this knowledge, little is known about how the imprinting strain influences vaccine responses. To investigate the immune responses of the imprinted host to split-virion vaccination, we imprinted ferrets with a sublethal dose of the historical seasonal H1N1 strain A/USSR/90/1977. After a +60-day recovery period to build immune memory, ferrets were immunized and then challenged on Day 123. Antibody specificity and recall were investigated throughout the time course. At challenge, the imprinted vaccinated ferrets did not experience significant disease, while naïve-vaccinated ferrets had significant weight loss. Haemagglutination inhibition assays showed that imprinted ferrets had a more robust antibody response post vaccination and increased virus neutralization activity. Imprinted-vaccinated animals had increased virus-specific IgG antibodies compared to the other experimental groups, suggesting B-cell maturity and plasticity at vaccination. These results should be considered when designing the next generation of influenza vaccines.